Antioxidant Activity of Polyphenolic Compounds from Dalbergia odorifera T. Chen - Hou, Jian-Ping; Wu, Hou; Ho, Chi-Tang; Weng, Xin-Chu (Pakistan Journal of Nutrition, 2011)
Seven compounds were isolated from Dalbergia odorifera T. Chen and their antioxidant activities were studied with Oil Stability Index (OSI) method, reducing power and radical scavenging methods. The compounds were identified by spectroscopic methods as (1) pinocembrin (2) biochanin A (3) sativanone (4) biochanin B (5) naringenin (6) 3′-hydroxymelanettin and (7) eriodictoyl. Results showed that compounds 6 and 7 exhibited stronger antioxidant activity than commonly used synthetic antioxidant BHT in the presented study.